Pengaruh Investasi Pemerintah, Swasta, Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia - Muhammad Bagus Prasetyo; Anifatul Hanim; Fajar Wahyu Prianto (Jurnal Ekuilibrium, 2021)
Economic growth is one component of a country's economic development. Economic growth is an important component for sound economic activity. Where economic growth can be seen through the amount of GDP in a country. If you experience an increase in the amount of GDP, it is considered that the economy is experiencing growth. The problem that exists in Indonesia is that the rate of economic growth is unstable, which can experience growth or decline in its growth rate.This research was conducted to analyze how the influence of government, private, export and import investment on economic growth in Indonesia. By taking the research object in 2010-2019. The analysis tool used is the panel data method in the form of a fixed effect model. Hypothesis testing using F-test, t-test, coefficient of determination and classical assumption test. The results of the study state that the Government, Private, and Export Investment variables have a significant effect on Economic Growth while the Import variables have no significant effect on Economic Growth.